2015
DOI: 10.1039/c5sm01711d
|View full text |Cite
|
Sign up to set email alerts
|

Slip mechanisms in complex fluid flows

Abstract: The classical no-slip boundary condition of fluid mechanics is not always a valid assumption for the flow of several classes of complex fluids including polymer melts, their blends, polymer solutions, microgels, glasses, suspensions and pastes. In fact, it appears that slip effect in these systems is the rule and not the exemption. The occurrence of slip complicates the analysis of rheological data, although it provides new opportunities to understand their behavior in restricted environments delineating addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 157 publications
(265 reference statements)
3
70
0
Order By: Relevance
“…This stronger bonding to the steel surface usually results in wall adherence. The measured rheological data revealed wall slip even at low wall shear stress values. Other authors , who observed different slip mechanisms reported the first appearance of wall slip after exceeding a critical wall shear stress value. Generally, the experimentally determined slip velocity data correlate well with the dependencies predicted with the presented slip model in this paper, which considers a lubricating film between the die wall and the polymer melt. The experimentally obtained slip velocity increases with rising wall shear stress. The presented slip model predicts a power law dependency on wall shear stress.…”
Section: Resultssupporting
confidence: 85%
“…This stronger bonding to the steel surface usually results in wall adherence. The measured rheological data revealed wall slip even at low wall shear stress values. Other authors , who observed different slip mechanisms reported the first appearance of wall slip after exceeding a critical wall shear stress value. Generally, the experimentally determined slip velocity data correlate well with the dependencies predicted with the presented slip model in this paper, which considers a lubricating film between the die wall and the polymer melt. The experimentally obtained slip velocity increases with rising wall shear stress. The presented slip model predicts a power law dependency on wall shear stress.…”
Section: Resultssupporting
confidence: 85%
“…This is also consistent with the theoretical picture of a coil-stretch transition of the adsorbed chains occurring at the first monolayer of adsorbed polymer chains on the surface, and nearest neighbours in the next layer remain in the coiled conformation and entangled with other bulk chains. 23,43,74 In addition, we find that the average conformation of immobile chains reaches a higher level of molecular extension at Wi ¼ 22.6, compared to Wi ¼ 5.6 on ATPES surfaces. At the same Wi ¼ 22.6 on a regular glass, the DNA molecules still contain a signature of the preponderance of the coil-sized chain configurations during flow.…”
Section: -7mentioning
confidence: 72%
“…Despite the relevance and importance of wall slip in polymer flow, the molecular mechanisms of wall slip remain poorly understood. 23 Both the microstructure and the origin of wall slip can vary significantly depending upon the nature of the interaction between the polymer chain and the solid surface. The main objective of this work is to fundamentally address the molecular mechanisms of slip of the entangled polymer at different surface conditions (with strong and weak interactions) in the strong flow regime.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations